APPLICABILITY OF BACTERIAL ENDOTOXIN TEST (BET) FOR SOME RADIOPHARMACEUTICAL STERILE KITS BY THE USE OF TACHYPLEUS AMEBOCYTE LYSATE (TAL) - Putra, Amal Rezka; Lestari, Enny; Kurniasih, Dede; Karyadi, Karyadi; Sarmini, Endang; Aries, Arni (Sanata Dharma University, 2019)
The application of bacterial endotoxin test (BET) using TAL reagent on radiopharmaceutical kits is very important to conduct. The radiopharmaceutical kits that will be tested are macro aggregated albumin (MAA), tetrofosmin and ethambutol kits. Endotoxin testing stage was TAL 0.25 EU/mL verification test, inhibition/enhancement test, and endotoxin test for sample. Pyrogen testing using rabbits was also performed as a comparison test. The results of the TAL reagent verification test were all samples showed values corresponding to the standards of 2? = (+), 1? = (+), 1/2? = (-), 1/4? = (-), and negative water control (NWC) = (-). Furthermore, inhibition/enhancement tests for MAA, tetrofosmin, and ethambutol products show non-inhibiting or gel-inducing results, which are in accordance with acceptability standards, so that the samples can be tested using TAL reagents. The pH measurement results in each sample were MAA of 6.0, tetrofosmin of 7.0, and ethambutol of 8.0. The results of MAA, tetrofosmin, and ethambutol product testing were a sample = (-), positive product control (PPC) = (+), positive water control (PWC) = (+), and NWC = (-). In addition, the results of pyrogen testing also showed negative for MAA, tetrofosmin, and ethambutol.